Constructions of post-Yugoslav identities in contemporary Slovenian film - Majsova, Natalija (Acta Histriae, 2021)
This article discusses the construction of Slovenian national identity in relation to memories of the period of Socialist Yugoslavia and its dissolution in the context of contemporary Slovenian cinematography (1991–2021). The dynamic of forgetting and remembering Socialism and Yugoslav identity is presented with the help of an in-depth analysis of representations, reception and contexts of production contexts of select representative cases: Outsider (1997), the most popular Slovenian feature film of the 1990s, the mockumentary Houston, We Have a Problem! (2016) and the co-production Parada (2011). The article demonstrates that films are repositories and re-examiners of national and regional policies, trauma, and reinterpretations of history and identities. As such, they are important objects for analyzing processes of remembering memory processes and transformations of the attitudes towards the Slovenian recent past.
Keywords: kulturni spomin; nostalgija; oblikovanje identitet; slovenska nacionalna identiteta; slovenski film; socializem; travma